Variable training does not lead to better motor learning compared to repetitive training in children with and without DCD when exposed to active video games. (March 2017) - Bonney, Emmanuel; Jelsma, Dorothee; Ferguson, Gillian; Smits-Engelsman, Bouwien
Highlights: Different practice schedules (variable or repetitive) do not significantly impact the amount of learning. Children with DCD and TD children learn motor skills at the same rate when exposed to active video games. Although there is specificity of training effect, this does not lead to differences in transfer in children with DCD and TD children. Abstract: Background: Little is known about the influence of practice schedules on motor learning and skills transfer in children with and without developmental coordination disorder (DCD). Understanding how practice schedules affect motor learning is necessary for motor skills development and rehabilitation. Aims: The study investigated whether active video games (exergames) training delivered under variable practice led to better learning and transfer than repetitive practice. Methods and procedures: 111 children aged 6–10 years (M = 8.0, SD = 1.0) with no active exergaming experience were randomized to receive exergames training delivered under variable (Variable Game Group (VGG), n = 56) or repetitive practice schedule (Repetitive Game Group (RGG), n = 55). Half the participants were identified as DCD using the DSM-5 criteria, while the rest were typically developing (TD), age-matched children. Both groups participated in two 20 min sessions per week for 5 weeks. Outcomes and results: Both participant groups (TD and DCD) improved equally well on game performance. There was no significant difference in positive transfer to balance tasks between practice schedules (Repetitive and Variable) and participant groups (TD and DCD). Conclusions and implications: Children with and without DCD learn balance skills quite well when exposed to exergames. Gains in learning and transfer are similar regardless of the form of practice schedule employed. What this paper adds: This is the first paper to compare the effect of practice schedules on learning in children with DCD and those with typical development. No differences in motor learning were found between repetitive and variable practice schedules. When children with and without DCD spend the same amount of time on exergames, they do not show any differences in acquisition of motor skills. Transfer of motor skills is similar in children with and without DCD regardless of differences in practice schedules.